LEX AQUILIA IN MEDIEVAL SERBIAN LAW - Polojac, Milena (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
The author, studying the reception of Roman law in medieval Serbia, examines the case of famous lex Aquilia. First, Roman legal sources were analysed, then their transformation through Byzantine law and finally their reception in the Serbian medieval law. Lex Aquilia and its interpretation by Roman iurists is present in the medieval Serbian law in the very modest way. It is reduced down to only two or three fragments respectively, from the Justinian`s Codex and the Digest title 9.2. Ad legem Aquiliam. The fragments are concerned with the cases of damage caused by killing pecora C.3.35.5 and by burning - urere: D.9.2.30.3 (Paulus libro 22 ad edictum), D.9.2.49.1 (Ulpianus libro nono disputationum). The above mentioned fragments first found their place in the Byzantine compilations (Ekloga, Proheiros Nomos, and the Syntagm of Matthew Blastares). Then they became part of the Serbo-Byzantine compilations: the Nomocanon of Saint Sava (ca. 1219), chapter 55 called City-statute (translation of Proheiros Nomos), the Syntagm of Matthew Blastares (14. century) translated into Serbo-Slavonic language (E-7). The abridged version of the Syntagm of Matthew Blastares (E-4) was made in medieval Serbia by reducing ecclesiastical law and preserving civil and criminal provisions. The compilation entitled Constantine Justinian’s Law is based mainly on the Syntagm of Matthew Blastares. The way of reception shows decay and vulgarisation of the Justinianic tradition. For example, above mentioned texts were associated with criminal law and merged with the fragments from the Digest’ book 47, title 9 (De incendio ruina naufragio rate nave expugnata), and the cases of incendium - D.47.9.9 Gaius libro quarto ad legem duodecim tabularum, D.47.9.11 Marcianus libro 14 institutionum. The fragments of Roman iurists were abridged by dropping out all teorethical issues. Only pure casuistry is preserved. Key words: Lex Aquilia. - Reception.- Byzantine compilations.- Serbo-Byzantine compilations.